2001
DOI: 10.1002/1522-2683(200109)22:16<3458::aid-elps3458>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous migration of hyaluronic acid oligomers in capillary electrophoresis: Correlation to susceptibility to hyaluronidase

Abstract: During high-resolution capillary electrophoresis analysis in an electrolyte solution containing a neutral polymer, small oligomers of regularly arranged acidic polysaccharides such as hyaluronic acid and N-acetylneuraminic acid polymers showed reversal of the migration order. This anomalous migration was well correlated with their reported biological activity. In the present study, we analyzed hyaluronidase action on the purified hyaluronic acid oligomers using capillary electrophoresis and found that hydrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although we reported the analysis of native HA preparations and HA oligomers using capillary electrophoresis with photometric detection, the analysis requires ca. 1 h [14,[22][23][24]. In contrast, the present method using microchip electrophoresis is completed within a few minutes.…”
Section: Analysis Of Hyaluronic Acid (Ha)mentioning
confidence: 86%
“…Although we reported the analysis of native HA preparations and HA oligomers using capillary electrophoresis with photometric detection, the analysis requires ca. 1 h [14,[22][23][24]. In contrast, the present method using microchip electrophoresis is completed within a few minutes.…”
Section: Analysis Of Hyaluronic Acid (Ha)mentioning
confidence: 86%
“…These data indicate that hyaluronidase did not cleave HA 8 to HA 6 and HA 2 but produced two molecules of HA 4 . These characteristic patterns of enzyme action were in good agreement with those as reported previously [20]. It should be noticed that the time required for each run was only 3 min, and ME made it possible to monitor the reaction course using a portion of the reaction mixture.…”
Section: Digestion Of Hyaluronic Acid 20 Mer (Ha 20 ) With Hyaluronidasementioning
confidence: 99%
“…17 Capillary electrophoresis was performed on a Beckman P/ACE 5010 using a fused silica capillary (50 mm id, effective length, 40 cm, J&W Scientific) in 50 mM Tris-borate buffer (pH 9.3) containing 100 mM SDS. 18 Applied potential was 14 kV, and the operation temperature was 30 °C. Sample solutions were injected by pressure method (0.5 psi, 10 s).…”
Section: Apparatusmentioning
confidence: 99%
“…We also reported that a defined size (decamer or larger) is necessary to form a unit structure of HA. 16,18,30 This is the reason why GAGs should have enough size to be captured by PL-polymer. It is also reasonable that PL-polymer show higher affinity to a highly sulfated GAG such as HP than a non-sulfated GAG such as HA.…”
Section: Effect Of Molecular Masses Of Ha On Capturing Of Ha Moleculesmentioning
confidence: 99%